2023
DOI: 10.12688/f1000research.133314.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of family-centered care interventions on well-being of caregivers of children with cerebral palsy: a systematic review

Abstract: Background: Caring for a child with long-term functional limitations can have a negative impact on the physical and psychological well-being of the caregiver. Family-centered care (FCC) interventions have the potential to empower caregivers and contribute to their well-being. This systematic review aimed to synthesize existing evidence on the effectiveness of FCC interventions in improving the well-being of caregivers of children with cerebral palsy (CP), and identify the key components of such interventions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The sample size in these studies varied from n=21 to n=251, for the parents and children with CP. Table 1 58 provides an overview of the characteristics of each study, while the TIDieR checklist (Extended data, dataset 3) details the interventions used in each trial. There was a lot of heterogeneity in the focus of interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size in these studies varied from n=21 to n=251, for the parents and children with CP. Table 1 58 provides an overview of the characteristics of each study, while the TIDieR checklist (Extended data, dataset 3) details the interventions used in each trial. There was a lot of heterogeneity in the focus of interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the risk of bias domain assessing outcome assessor’s awareness of intervention and its influence on outcome was rated as ‘probably no’ to avoid categorizing as high-risk of bias on this specific basis except for three articles which had mentioned as outcome assessor were blinded. Table 2 57 represents the results of the CASP Randomised Controlled Trial Standard Checklist. The majority of the studies showed limitations in allocation concealment, investigator and participant blinding, and reporting adverse effects and costs of intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation